PERBANDINGAN PENGUJIAN VISKOSITAS LUBE OIL DENGAN MENGGUNAKAN METODE ASTM D-445 DAN ASTM D-7042 - Fahmi, Miraz’hul; Pasaribu, Subur P. (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Lubricant is one of the supporters so that the machine can operate optimally within a certain period of time so that the right viscosity is needed. This literature study aims to determine the appropriate method of testing the viscosity of a product. There are two different methods for testing viscosity, namely the ASTM D-445 and ASTM D-7042 methods. In this literature study, operational methods and scope of testing are compared between ASTM D-445 and ASTM D-7042 methods. Based on the results of the literature study, the ASTM D-445 method has a different method from ASTM D-7042. In ASTM D-445 it is a test to determine kinematic viscosity (ν) while in ASTM D-7042 it is a test which includes determining dynamic viscosity (η) and density (ρ). This literature study shows that the ASTM D-7042 method is very effective in the food industry, whereas the ASTM D-445 method is found to be very effective in the natural gas processing industry. Keywords: ASTM D-445, ASTM D-7042, Dynamic viscosity, Kinematic viscosity.